Colorectal sessile serrated lesion detection using linked-color imaging versus narrow-band imaging: a parallel randomized controlled trial - Li, Jun; Chen, Kan; Wei, Yunlei; Zhang, Di; Wang, Yuxin; Hou, Xiaojia; Wu, Ruijin; Peng, Kangsheng; Li, Lei; Huang, Chao; Wang, Yilong; Xun, Linjuan; Liu, Feng (Endoscopy, 2023)
Background Previous studies have reported the effectiveness of narrow-band imaging (NBI) and linked-color imaging (LCI) in improving the detection of colorectal neoplasms. There has however been no direct comparison between LCI and NBI in the detection of colorectal sessile serrated lesions (SSLs). The present study aimed to compare the effectiveness of LCI and NBI in detecting colorectal SSLs.Methods A prospective, parallel, randomized controlled trial was conducted. The participants were randomly assigned to the LCI or NBI arms. The primary end point was the SSL detection rate (SDR).Results 406 patients were involved; 204 in the LCI arm and 202 in the NBI arm. The total polyp detection rate, adenoma detection rate, and SDR were 54.2 %, 38.7 %, and 10.8%, respectively. The SDR was not significantly different between the LCI and NBI arms (12.3 % vs. 9.4 %; P = 0.36). The differences in the detection rate and the per-patient number of polyps, adenomas, diminutive lesions, and flat lesions between LCI and NBI also were not statistically significant. Multivariate analysis showed that LCI and NBI were not independent factors associated with SDR, whereas Boston Bowel Preparation Scale score (odds ratio [OR] 1.35, 95 %CI 1.03–1.76; P = 0.03), withdrawal time (OR 1.13, 95 %CI 1.00–1.26; P = 0.04), and operator experience (OR 3.73, 95 %CI 1.67–8.32; P = 0.001) were independent factors associated with SDR.Conclusions LCI and NBI are comparable for SSL detection, as well as for the detection of polyps and adenomas.